2007
DOI: 10.1002/jssc.200700044
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sugars and alditols in tobacco with high performance anion‐exchange chromatography

Abstract: Sugars, alditols, and alcohols in tobacco products were quantified utilizing a method of high-performance anion-exchange chromatography-pulsed amperometric detection (HPAEC-PAD). The optimized analytical method can be used to classify different tobaccos and control the quality of tobaccos. To substantiate the applicability of the method, the analysis of 27 tobacco samples with satisfactory linearity, repeatability, and accuracy had been demonstrated. Compared with some other analytical methods for tobacco, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Traditionally, solvent extraction and solid-phase extraction purification are the most widely used treatment methods for the analysis of the main carbohydrates in tobacco [3][4][5][6][7][8][9][10]. However, drawbacks such as the need for multiple extractions and the large required volume of toxic organic solvent make solvent extraction expensive, time-consuming, and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, solvent extraction and solid-phase extraction purification are the most widely used treatment methods for the analysis of the main carbohydrates in tobacco [3][4][5][6][7][8][9][10]. However, drawbacks such as the need for multiple extractions and the large required volume of toxic organic solvent make solvent extraction expensive, time-consuming, and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the main carbohydrates in tobacco and tobacco products is typically accomplished through the use of segmented flow analysis (SFA) [3], gas chromatography (GC) with derivatization [4], high-performance liquid chromatography (HPLC) [5][6][7][8], and ion chromatography (IC) [9][10]. Compared with the other methods, GC with derivatization shows some unique advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Such differentiation is important because federal tax rates in the United States differ across tobacco product categories and sub-categories, and product characteristics could impact regulatory efforts. Moreover, sugar levels are known to differ among certain product types [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Existing methods for humectant detection range from IC to GC to GC-MS [2, 10]. Tang et al developed an IC method, and applied it to analyze 12 sugars, alditols, and humectants in tobacco [9]. Rainey, et al concluded that a GC-MS method can compensate for the inadequate chromatographic resolution between the analyzed humectants [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation